Música para grupos amadores: a linguagem contemporânea como ferramenta de aprimoramento técnico-musical - Lucas Duarte Neves (2017)
This thesis analyses and describes the process of composition and performance of five pieces written for the Sociedade Musical Santa Cecilia de Sabarás Chamber orchestra (Santa Cecilia Orchestra). These compositions were made with the intent of contributing to the expand of the expressive possibilities and tecnical proficiency of the group through the application of allusive musical languages to the repertoire of the Concert Music of XX century. The process of composition was analyzed through the concept of Constraints in Musical Composition and, as of the technical limitations of Santa Cecilia Orchestra, attached to the technical-musical diagnostic. This diagnostic pointed, besides the historical-cultural context of the group, the technical elements that needed improvement and that would be applied to the compositions. All the process of rehearsal was too described and analyzed, verifying the effectiveness through the possibility of extension of the musical universe and expressions of the musicians developed by the execution of these pieces. The four pieces composed will be examples to the insertion of new languages to the repertoire of musical groups similar to Santa Cecilia Orchestra.